The illusion of inclusion: Agenda 21 and the commodification of Aboriginal culture in the Vancouver 2010 Olympic Games. (1st June 2016) - Forsyth, Janice
This article investigates the discourse about Aboriginal people benefitting from the 2010 Olympic Games and argues there was nothing fundamentally new about Aboriginal involvement in Vancouver, except for an unprecedented mobilization of Aboriginal bodies, land and insignia. In this regard, Aboriginal inclusion in 2010 was definitely different from past Games. There were more Aboriginal performers, artists and volunteers, more cultural imagery in strategic locations, and more indigenous merchandise for sale than ever before. Yet, in spite of their increased visibility, the power relations sustaining historic inequities between Olympic organizers and Aboriginal people remained largely unchanged. Indeed, a closer look at how Aboriginal people were involved in the Vancouver Games, the promises made to them, and the legacies that actually materialized, suggests the present day arrangement for Aboriginal people within the Olympic industry has actually worsened.